A complementary micro Coronavirus model under uncertainty and utility - James P. Gander (The University of Utah, Department of Economics, 2020)
A micro decision-making utility model under uncertainty is presented as a complementary foundation for macro coronavirus models. The micro model consists of two functions, a risk averse utility function depending on wellness and a wellness random output which is a function of the input variable called "treatment" consisting of such elements as social distance, washing hands, wearing a face mask, and others. The decision maker selects a level of treatment that maximizes her/his expected utility, given the probabilities of the respective outputs. The focus is on how changes in a person's psychological attitude towards the macro determined (announced) probabilities affects the optimum results of the model. Such changes create a micro-macro dynamic interaction which is briefly outlined. A short discussion of the model's behavioral implications for health policy is also given.
Keywords: C02; C61; D11; D20; D81; D84; D91; I1; I18; 330; Utility; Uncertainty; Risk Averse; Wellness Output; Treatment Inputs; Coronavirus; Psychological Risk Attitude; and Dynamic Interactions